Prescribing or dispensing medication represents the best opportunity for GPs and pharmacists to engage older people in alcohol‐related clinical conversations. (12th February 2016) - Wilkinson, Celia; Dare, Julie; French, Michelle; McDermott, Marie‐ Louise; Lo, Johnny; Allsop, Steve
Abstract: Objectives: This research aimed to identify older Australian drinkers' knowledge about Australian Alcohol Guidelines and their beliefs about the risks and benefits of alcohol; their recall of alcohol‐related issues being raised with them by their community pharmacist and General Practitioner (GP); and their receptiveness to alcohol‐related information being provided by either health professional. Methods: This research was conducted in Perth, Western Australia. Flyers calling for participants were placed in local health and service centres, and advertisements were placed in local media. Participants who met eligibility requirements were posted a survey pack ( n = 190) including an information letter, consent form, quantitative survey, and return addressed, postage paid envelope. 188 people aged over 60 years returned completed questionnaires. Key findings: Women were more familiar with national alcohol guidelines, and were more conservative about the potential health benefits of alcohol. While 90% of participants were receptive to their GP asking about their alcohol use, only 30% of men and 20% of women recalled their GP raising this issue with them in the prior 12 months. Of these, high‐risk drinkers were six times more likely than low‐risk drinkers to have been asked by their GP. Likewise, 50% of men and 65% of women were receptive to having alcohol‐related health conversations with their community pharmacist, but less than 4% recalled their pharmacist raising this issue. Participants were most receptive to receiving information about alcohol‐medication interactions. Conclusions: This research highlights that prescribing and dispensing medication represents the ideal opportunity for health professionals to deliver alcohol‐related information to older people.